CYFRA 21-1 in Lymph Node Fine Needle Aspiration Washout Improves Diagnostic Accuracy for Metastatic Lymph Nodes of Differentiated Thyroid Cancer - Jeongmin Lee (Cancers, 2019)
Fine needle aspiration cytology (FNAC) and washout thyroglobulin (Tg) measurements are the standard for evaluating a metastatic lymph node (LN) in thyroid cancer. However, patients rarely benefit from these procedures due to false results. This study aims to identify a reliable biomarker that significantly improves the diagnosis of metastatic LNs, in addition to FNAC and washout Tg. This study analyzed 130 LNs that were suspected to have metastases on thyroid ultrasonography, from June 2016 to December 2017. All subjects underwent FNAC, washout Tg measurements and a new biomarker, washout Cytokeratin fragment 21-1 (CYFRA 21-1) measurement. The final LN outcomes were confirmed by surgical histology, repeat FNAC, or follow-up image. The diagnostic values of the presence of washout CYFRA 21-1 for diagnosing metastatic LNs were evaluated according to final LN outcomes. Among the 130 LNs, 42 were metastatic lesions and 88 were benign. The washout CYFRA 21-1 levels were significantly higher in metastatic LNs than in benign LNs. In contrast to the findings of washout Tg, washout CYFRA 21-1 showed little overlap between benign and malignant LNs, and its diagnostic cutoff values were not affected by surgery. The combinations of FNAC and washout CYFRA 21-1 showed higher sensitivity (91.9%), specificity (96.5%), negative predictive value (98.8%), and diagnostic accuracy (94.2%) than FNAC with washout Tg. The combination of FNAC, washout Tg, and washout CYFRA 21-1 showed the best sensitivity (98.8%). When washout CYFRA 21-1 was applied to the discordant results that were observed between FNAC and washout Tg, 20 of 22 LNs were correctly diagnosed. Washout CYFRA 21-1 measurements in thyroid LNs provide a diagnostic modality.